2013
DOI: 10.1007/s12195-013-0297-4
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Chromosome Speeds in Mitosis

Abstract: When chromosome are being separated in preparation for cell division, their motions are slow (~16 nm/s) relative to the speed at which many motor enzymes can move their cellular cargoes (160–1000 nm/s and sometimes even faster) and at which microtubules (MTs) depolymerize (~200 nm/s). Indeed, anaphase chromosome speeds are so slow that viscous drag puts little load on the mechanisms that generate the relevant forces [35]. Available evidence suggests that chromosome speed is due to some form of regulation. For … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
10
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 58 publications
(67 reference statements)
2
10
0
Order By: Relevance
“…The small displacement changes from metaphase to early anaphase suggested that individual chromosomes maintained their relative position to another and within the mitotic chromosome mass. These results also corroborate previous studies showing limited movements when chromosomes are attached to the mitotic spindle (19, 27, 28). Therefore, the absence of major displacement changes at metaphase to midanaphase allowed us to quantitatively map individual chromosomes in a 3D coordinate system (Fig.…”
Section: Resultssupporting
confidence: 92%
“…The small displacement changes from metaphase to early anaphase suggested that individual chromosomes maintained their relative position to another and within the mitotic chromosome mass. These results also corroborate previous studies showing limited movements when chromosomes are attached to the mitotic spindle (19, 27, 28). Therefore, the absence of major displacement changes at metaphase to midanaphase allowed us to quantitatively map individual chromosomes in a 3D coordinate system (Fig.…”
Section: Resultssupporting
confidence: 92%
“…This is similar to pole-pole separation by outward sliding of interpolar MTs in diatoms, fission yeast, grasshopper, and Drosophila embryo ( Brust-Mascher et al., 2009 , Khodjakov et al., 2004 , Leslie and Pickett-Heaps, 1983 , Tolic-Norrelykke et al., 2004 ). Our results support a view that the pushing forces from the midzone interpolar fibers, combined with the regulation of MT dynamics at the kinetochore and the pole, define the speed of chromosome and centrosome separation in human cells, as previously discussed ( Betterton and McIntosh, 2013 ). On the contrary, severance of the spindle midzone accelerated pole separation during anaphase B in Nectria haematococca , PtK2 cells, and C .…”
Section: Discussionsupporting
confidence: 91%
“…The different force-velocity relationships at 254 kinetochore-microtubule plus-ends in mammals and yeast kinetochore particles could, 255 for example, stem from differences in applied forces, kinetochore architecture (Long et 256 al., 2019), or additional regulation in cells. The molecular basis of potential "governors" 257 of k-fiber plus-end polymerization velocity has been a long standing question (Nicklas,258 1983; Betterton and McIntosh, 2013;Long et al, 2017), and our findings suggest that in mammals this molecular "governor" is not mechanically regulated. Notably, force not 260 regulating mammalian k-fiber polymerization velocity (Fig.…”
mentioning
confidence: 60%
“…There was no correlation between k-fiber growth rate 133 and pulling speed ( Fig. 2H), suggesting either that force was dissipated before reaching 134 the k-fiber's ends or that force does not regulate its maximum growth rate (Nicklas, 135 1983(Nicklas, 135 , 1988Skibbens and Salmon, 1997;Betterton and McIntosh, 2013). Further, the k-136 fiber growth rate did not vary with the proximity of the microneedle to the plus-end 137 (Spearman R coefficient = 0.08, p = 0.76, Fig.…”
mentioning
confidence: 99%